(untitled) (Research, Society and Development, 2021)
The study aimed to verify the prevalence of gingival bleeding in children in early childhood at a children’s dental clinic, aiming to highlight the importance of promoting oral health and seeking to subsidize dental professionals to diagnose and help prevent gingivitis in children. This is a cross-sectional, descriptive and quantitative study, carried out on the premises of the Clínica-Escola de Odontologia of Centro Universitário de João Pessoa (UNIPÊ). The sample was obtained, in a non-probabilistic way for convenience, consisting of 100 records of children aged 3 to 6 years. The information was recorded on a form for statistical treatment of the data. Regarding gender, 53% of the children were male and 47% female. The occurrence of gingival bleeding in early childhood children was observed in 63% of the sample and 37% did not present any gingival bleeding. In 49% of the children, the Gingival Bleeding Index (ISG) score was between 1 and 10%; in 11% the ISG score was obtained between 11 to 25% and only 3% obtained the ISG score between 26 and 50%. Regarding the presence of biofilm, children aged five and six years had a higher percentage of the Oral Hygiene Index (IHB), as well as ISG. It was concluded that the occurrence of gingival bleeding in early childhood children in this research was high (63%), with its occurrence not influenced by sex, but associated with increasing age. The presence of bleeding was shown to be associated with the accumulation of biofilm.